STRATEGI KOMUNIKASI SAPULIDI CENTER DALAM MENSOSIALISASIKAN PROGRAM PENGEMBANGAN INDUSTRI KREATIF DI KOTA PEKANBARU (Studi Deskriptif pada Subsektor Industri Kuliner eCafe Sapulidi Center) - Rika Oktalia; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The creative industry is considered to be more important in supporting prosperity of economy. Sapulidi Center is Self-supporting institution of Society and has function as the center of the development of creative industry by establishing a place of creativity and creative industries development program in the form of UMKM such as cafe. The aim of this research is to know the strategy of communication that is done by Sapulidi Center in socializing culinary industry development program eCafe Sapulidi Center in pekanbaru.The approach of this research is descriptive method, with the approach of communication model Lasswell as the basic theory and and strategic communication model that is supported by Effendy. The subjects of research are coaches and staff of Sapulidi Center, schoolchildren / students, community groups and government agencies by using purposive sampling techniques, informant obtained as many as five people. Data collection techniques are observation, interview,andkkdocumentation.The result of research: The communication strategy that is undertaken by Sapulidi Center is by determining the target audience: schoolchildren / students, community groups and government agencies. Factors that are considered in designing the message is: message content, message structure, and message format. Communication media used face to face communication media and mass media both print and electronic media (RTV, Riau Pos, Tribun, Online media, and social media) are used to inform the news about the activities of Sapulidi Center. The role of communicators in the communication are the appeal (trust), the charismatic (emphatic) and the credibility of sources (skills and knowledge) in conveying the message.Keywords: Communication strategy, creative industry, culinary industry, Sapulidi Center